Pemanfaatan Ekstrak Daun Zodia dan Rosemary sebagai Anti Nyamuk dalam Bentuk Refill dengan Memanfaatkan Limbah Mat Elektrik - Laksono, Budi; , Dr. Siti Chalimah, M.Pd (2015)
Aedes aegypti is one of the types of insects that harm humans because as the main vector of viruses that cause hemorrhagic fever (DB) which can kill humans. Insect mosquito is more dangerous to human health than other types of insects. Mixing Zodia and Rosemary leaf extract can be used as a mosquito .. The purpose of research is to determine the effectiveness of Zodia and Rosemary leaf extract as a mosquito by utilizing waste electrical mat against paralysis and death of Aedes aegypti. The research method was performed using the experimental design completely randomized design (CRD), consists of two factors: a comparison between Zodia and Rosemary Leaf and second soaking time. In collecting the data by calculating the Aedes aegypti mosquito which paralyzed in the next 20 minutes, the value of mortality is calculated after fainting diholding mosquitoes for 24 hours. Analysis of data using Abbot formula and calculate the percentage of mortality of Aedes aegypti. Results obtained almost all treatments have KT50 values and mortality except negative control immersion with clear water for 18 hours (P0L1). Based on the results obtained overall the most effective treatment of crippling and deadly Aedes aegypti is treated by soaking the electric mat with a mixture ratio Zodia and Rosemary extract 2: 1 by immersion for 18 and 24 hours. Key words : natural insecticide, zodia, rosemary, Aedes aegypti mosquito, mortality, KT50